Healthy dried baby corn silk vinegar production and determination of its main organic volatiles containing antimicrobial activity - Warawut Krusong (2020)
© 2019 Elsevier Ltd Dried baby corn silks (DBCS) are an underutilized by-product and a good source of active compounds. Analysis of DBCS showed 5.15 ± 0.21 mg GAE mL−1 total phenolic compounds, 4.24 ± 0.08 mg GAE mL−1 total flavonoid compounds and an antioxidant activity of 45.98 ± 7.89% inhibition for free radical scavenging DPPH, 91.33 ± 0.33% inhibition for ABTS and 44.17 ± 0.53% chelating effect for FIC. In the acetification process, 15 g L−1 (w/v) DBCS was suitable for wine making resulting in 94 ± 1 g L−1 alcohol. Subsequently, acetic acid (62 ± 1 to 75 ± 1 g L−1) was produced during 9 cycles of semi-continuous processing. The remaining active compounds, in both wine and vinegar, were also determined and a significant reduction (p ≤ 0.5) of total phenolic compounds and antioxidant activity from DBSC was observed, which were higher in vinegar than in wine. Among volatile organic compounds found using GC-MS, only five of the main compounds, which had antimicrobial properties, were found in both wine and vinegar. They were acetic acid, ethyl ester; 1-butanol, 3-methyl-, acetone; 1-butanol, 3-methyl-; hexanoic acid and octanoic acid. Results indicated that DBCS contained compounds that were beneficial to health and therefore could be a functional food and provide additional beneficial applications as an antimicrobial agent.